Contribution béninoise à la géographie - Noukpo Agossou (Cybergeo, 2010)
This article continues a double project to define the places of production of university geography in Benin and to give Beninese geography a mark of identity. This geography is the work primarily of about thirty Beninese scholars, supported by as many assistants of research and lecturers, without forgetting all the geographers who operate in various public and private institutions. This geography which initially came from the ex-university of Dahomey in 1971 continues little by little in the sub region, through work recognized in many fields. After having tried a definition of this geography, we shall present some of its fundamental works, then its contribution to the development of the country, the cover rate of the national territory by research, the modes of articulation between secondary and university geography education, etc. Taking into account the limited available means to the Department of Geography and Land Planning, the quasi-exponential growth of students poses more problems than it testifies the vitality of this geography.